2020
DOI: 10.12973/eu-jer.9.2.809
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish Version of the Teacher Efficacy for Inclusive Practice (TEIP) Scale: Adaptation and Psychometric Properties

Abstract: The Teacher Efficacy for Inclusive Practice (TEIP) scale is an instrument created by Sharma et al. to assess efficacy of instruction in inclusive settings. Despite its increase in use, the TEIP has not been validated with a Spanish teacher population. The aim of this study was to: (1) analyze the psychometric properties and factor structure of the TEIP scale in a sample of Spanish preservice teachers (N = 475; 80% female, 20% male), and (2) examine the level of self-efficacy for inclusive practices that teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Exceptions were Item 6 ('I am confident in my ability to get students to work together in pairs or in small groups') and Item 12 ('I can make my expectations clear about student behavior'), which had cross-loadings >0.3 on other factors. Of these two items, only Item 12 has been observed to cause misfit in several other studies (Alnahdi, 2019;Cardona-Molto et al, 2020;Malinen, Savolainen, Engelbrecht, et al, 2013;Sharma & Jacobs, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Exceptions were Item 6 ('I am confident in my ability to get students to work together in pairs or in small groups') and Item 12 ('I can make my expectations clear about student behavior'), which had cross-loadings >0.3 on other factors. Of these two items, only Item 12 has been observed to cause misfit in several other studies (Alnahdi, 2019;Cardona-Molto et al, 2020;Malinen, Savolainen, Engelbrecht, et al, 2013;Sharma & Jacobs, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Slight adaptations, such as discarding certain items, were nevertheless often necessary to reach an adequate model fit (e.g. Aiello et al, 2018; Cardona‐Molto et al, 2020; Malinen, Savolainen, & Xu, 2013; Miesera et al, 2019). Initial CFAs using data from our sample of teachers in Switzerland also revealed that the original solution with the three correlated factors as proposed by Sharma et al (2012) failed to reach an adequate fit to the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially due to the cultural characteristics of education, the same scales have been observed to yield different results in different cultures. There are numerous studies on the adaptation of a scal e developed in a certain culture to a different culture in the literature (Cam et al, 2012;Cardona-Molto et al, 2020;Teo & Chai, 2012).…”
Section: Introductionmentioning
confidence: 99%